Kajian pemalsuan bekatul dan tepung ikan di Wilayah Jawa Tengah - Cahya Setya Utama; Bambang Sulistiyanto (Universitas Sebelas Maret, 2021)
Objective: The research aimed examine the quality adulteration of bran and fish meal in the Central Java region.Methods: The materials used are rice bran and fish meal originating from 17 regions in Central Java which include Rembang, Jepara, Batang, Solo, Boyolali, Pekalongan, Kendal, Temanggung, Magelang, Ungaran, Pati, Purwodadi, Demak, Salatiga, Kudus, Klaten and Semarang. The research method uses descriptive method. Sampling was carried out by purposive random sample to represent the area of the area used as the research site (10 shops in 1 region with different districts and / or villages). Measurement of the parameters of adulteration on bran used Phloroglucinol test, buoyancy test and specific gravity test, while fish meal used urea test.Results: The results showed that the bran which was tested for Phloroglucinol and positive buoyancy was faked by adding husks, and was found in the Pati and Demak areas. Density test describes rice bran with non-standard density in Purwodadi, Kendal, Temanggung, Demak and Semarang. Fish meal adulteration occurred in the Boyolali and Pati regions with positive urea content.Conclusions: The conclusion of this research is that good quality of rice bran based on phloroglucinol test, husk floating test and bulk density test were found in Rembang, Jepara, Solo, Boyolali, Magelang, Ungaran, Salatiga and Kudus areas, the quality of fish meal indicated for adulteration based on the urea test was Pekalongan and Purwodadi areas.